Pengembangan Perangkat Pembelajaran Matematika Berbasis Discovery Learning untuk Memfasilitasi Kemampuan Koneksi Matematis Peserta Didik - Ilham Saputra; Armis Armis; Maimunah Maimunah (Universitas Muria Kudus, 2022)
The purpose of of this study is to determine the validity and practicality of a mathematics learning tools based discovery learning to facilitate the mathematical connection skills of students. This type of research is Research Development refer to 4D model.The development that the researchers carried out consisted of four stages, namely: (1) define; (2) design; (3) develop; (4) disseminate. The test subjects were 6 students of class X SMAN Plus, Riau Province. The research instrument used was a validity instrument in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans and student worksheet. The validation of the learning tools by three experts. The results of the validation of the experts stated that the products that succeeded in reaching the very valid category with an average result for the syllabus were 3,95, RPP 3,95 and LKPD 3,77. In addition, this mathematics learning tools meets the practical requirements in small group trials with an average student response questionnaire of 82,93% in the very practical category. Thus, the learning tools developed have met the valid and practical requirements to facilitate students' mathematical connection abilities